ARTEFAK RELIEF YEH PULU : MENGUNGKAP PERADABAN MASYARAKAT ZAMAN KERAJAAN BALI KUNO, DI INDONESIA - I Nyoman Lodra; I Wayan Swandi (Institut Seni Indonesia Yogyakarta, 2021)
This research is intended to reveal the life and civilization of the people in ancient Bali. The focus of the problem: 1) what is the structure of the Yeh Pulu Bedulu relief sculpture. 2) How was the life and civilization of the people in ancient Bali? 3) What are the heritage values of Ancient Bali? Objectives: 1) To describe the structure of Yeh Pulu Bedulu relief artifacts. 2) To describe the life and civilization of the people in ancient Bali. 3) Describe and know the values of the heritage of life and civilization in ancient Bali. Benefits: knowing the level of life and civilization of society and cultural characteristics in ancient Balinese times Method: descriptive qualitative, by parsing, analyzing, data obtained in the field. This research uses the theory of iconography, ecology, ethnographic approach, visual language and the study of structural analysis, themes, techniques, and materials. Data collection: observation, literature, and documents. Data source; primary, secondary.. Findings: revealing the life and civilization of Ancient Bali from Yeh Pulu relief artifacts in Bedulu. Penelitian ini dimaksud untuk mengungkap kehidupan dan peradaban masyarakat di zaman Bali Kuno. Fokus masalah: 1) bagaimana struktur pahatan arterfak relief Yeh Pulu Bedulu.2) Bagaimana kehidupan dan peradaban masyarakat di zaman Bali Kuno?. 3) Apa nilai-nilai warisan zaman Bali Kuno?, Tujuan: 1) Mendiskripsikan struktur arterfak relief Yeh Pulu Bedulu.2) Mendeskripsikan kehidupan dan peradaban masyarakat di zaman Bali Kuno. 3) Mendeskripsikan dan mengetahui nilai-nilai warisan kehidupan dan peradaban zaman Bali Kuno. Manfaat: mengetahui tingkat kehidupan dan peradaban masyarakat dan karakteristik budaya di zaman Bali Kuno Metode: deskriptif kualitatif, dengan mengurai, menganalisis, data didapat di lapangan. Penelitian ini menggunakan teori ikonografi, ekologi, pedekatan etnografi, bahasa rupa dan kajian analisis struktur, tema, teknik, dan bahan. Pengambilan data: observasi, kepustakaan, dan dokumen. Sumber data; primer, sekender.. Temuan: mengungkap kehidupan dan peradaban zaman Bali Kuno dari artefak relief Yeh Pulu di Bedulu.